A Study of Derivatives Usage in the UK Unit Trusts - Xia, Chong (2007)
This paper study the derivatives use by the most popular unit trusts among domestic equity and fixed interest categories in the UK between July 2004 and June 2007. As investors love winning trusts that have good performance, the objective of this paper is to investigate whether winning trusts employ derivatives more and what determine their derivatives usage. Moreover, due to the non-linear pay-off structure of derivatives and their theoretical functions in cost efficient and risk hedging, the research question whether derivatives usage has impact on risk profile of unit trusts as well as their performances is also examined. By applying one Logit regression model, the size and age are found significantly related to the decision to use derivatives. Also it is found that one third of the popular unit trusts use derivatives, which is higher than the results from prior papers that use normal sample. Through traditional risk-adjusted performance measure, Jensen's alpha and Sharpe Ratio, the whole sample show superior performance significantly. However, there is no evidence to exhibit that it is the use of derivatives that improve the performance of these popular unit trusts.